Clinical utility and cost effectiveness of a personal ultrasound imager for cardiac evaluation during consultation rounds in patients with suspected cardiac disease. Issue 7 (1st July 2003) - Vourvouri, E C; Koroleva, L Y; Ten Cate, F J; Poldermans, D; Schinkel, A F L; van Domburg, R T; Vletter, W B; Roelandt, J R T C
Abstract : Objective: To assess the clinical utility and cost effectiveness of a personal ultrasound imager (PUI) during consultation rounds for cardiac evaluation of patients with suspected cardiac disease. Methods: 107 unselected patients from non-cardiac departments (55% men) were enrolled in the study. After the physical examination the consultant cardiologist performed an echocardiographic study with a PUI. The final report was given instantly to the referring physician. All patients subsequently underwent a study with a standard echocardiographic device (SED). For each patient the consultant cardiologist noted whether the findings of the PUI were adequate for final diagnosis. The total cost when full echocardiography was used was compared with the cost when the PUI was used. The time interval from request to diagnosis was also compared. Results: In 84 (78.5%) patients no further examination with an SED was regarded as necessary. Twenty three patients (21.5%) required a further detailed examination with the SED because of the need for haemodynamic information. There was an excellent agreement for the detection of abnormalities between the two devices (96%). The total cost was €132 per patient with the SED and €75 per patient with the PUI. According to this study, the use of the PUI can lead to a 33.4% reduction of total cost. The mean time from request to diagnosis at the authors' institution was four days for the SED and instantly for the PUI, for additional potential cost savings. Conclusions: Immediate echocardiographic assessment during consultation rounds can lead to significant cost savings and can shorten the time to diagnosis.